Contemporary issues in political sciences - Elfatih A. Abdelsalam; Garoot S. Eissa (IIUM Press, 2011)
This book is written in response to an initiative to boost research at the International Islamic University Malaysia (IIUM). All the chapters in this book have been written by the academic staff of the Department of Political Science in IIUM. although there is no unified theme that links the eight chapters, the book strives in its entirely to reflect the four sub-areas of the discipline of Political Science, namely: International Relations, Comparative Politics, Public Administration and Political Theory.